High-tenacity flexible fiber cement board and method of making same

CN122916588APending Publication Date: 2026-10-16WUHAN BUILDING MATERIAL IND DESIGN & RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611178937.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]本发明的目的是克服现有技术中纤维水泥板材韧性不足、无法大幅度弯折、工业固废利用率低以及生产成本高的问题

Benefits of technology

[0022]This invention provides a high-toughness, bendable fiber cement board using a rigid, flexible, and plant fiber ternary composite toughening system, combined with appropriately graded quartz sand and a ternary solid waste-modified matrix structure. This breaks through the bottleneck of traditional fiber cement boards being brittle and inflexible. The board can achieve small-radius circular bending and repeated bending without cracking, significantly improving flexibility and deformation recovery. It is suitable for various curved and irregularly shaped building construction scenarios, broadening its applicability. Through the sulfate activation and micro-expansion effect of desulfurized gypsum, the density of the board matrix is ​​optimized, effectively compensating for board shrinkage deformation and completely solving the problems of warping, micro-cracking, and bending damage in traditional boards. The dimensional stability, flexural strength, and impact toughness of the board are significantly improved, resulting in a longer service life. Furthermore, this formula synergistically utilizes three industrial solid wastes: carbide slag, fly ash, and desulfurized gypsum. The high proportion of solid waste significantly reduces industrial solid waste accumulation pollution, replacing traditional high-energy-consuming cement raw materials, reducing carbon emissions from production, and fully meeting the industry requirements for low-carbon, green, and circular development of building materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of building materials, and provides a high-toughness bendable fiber cement board and a preparation method thereof.The high-toughness bendable fiber cement board comprises the following preparation raw materials in parts by weight: 12-25 parts of carbide slag, 35-44 parts of fly ash, 12-20 parts of desulfurization gypsum, 10-25 parts of quartz sand, 0.5-1.5 parts of alkali-resistant glass fiber, 0.8-1.5 parts of PVA fiber and 3-5 parts of wood pulp fiber.The fiber cement board adopts a ternary composite toughening system of rigidity, flexibility and plant fiber, is matched with adaptively graded quartz sand, and is combined with a ternary solid waste modified matrix structure, so that small-radius circular arc bending and repeated bending without cracking are realized, the flexibility and deformation recovery are greatly improved, and the fiber cement board can be adapted to various curved surfaces and special-shaped building construction.Through sulfate activation and micro-expansion effect of the desulfurization gypsum, the compactness of the board matrix is optimized, and the size stability, bending strength and impact toughness of the board are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically relating to a high-toughness bendable fiber cement board and its preparation method. Background Technology

[0002] Fiber cement board is a widely used new building material in architectural decoration, wall cladding, and ceiling construction. Currently, most mainstream fiber cement board products on the market use a single fiber reinforcement system, with ordinary cement and quartz sand as the core raw materials, and are manufactured using traditional molding processes. Existing traditional fiber cement boards have poor overall mechanical toughness, weak impact resistance, high brittleness, and are prone to cracking. They lack the ability to undergo significant bending deformation, and their overall flexibility and construction adaptability are insufficient, making them unsuitable for personalized and stylized architectural construction scenarios such as irregular ceilings, curved partitions, and arc-shaped building cladding, severely limiting their application scenarios. Furthermore, some fiber cement board products on the market still use asbestos fiber as the reinforcing base material. Asbestos fiber is a hazardous material that easily generates harmful dust during board production, construction, and subsequent use, causing serious damage to the human respiratory system and posing a significant health and safety hazard. This does not meet the current industry development requirements for green building materials and environmentally friendly buildings.

[0003] Furthermore, the raw material system of traditional fiber cement boards is simplistic and fails to utilize industrial solid waste. Large quantities of common industrial solid wastes, such as carbide slag, fly ash, and desulfurization gypsum, remain idle and unused in board manufacturing. This long-term accumulation of industrial solid waste not only occupies significant land resources but also easily leads to soil, water, and air pollution, causing serious resource waste and ecological burden. In terms of production costs, traditional board formulations heavily rely on high-grade cement and other expensive core raw materials, resulting in high raw material procurement costs. The accompanying production processes are cumbersome and redundant, leading to a low yield rate of boards and further increasing the overall production and manufacturing costs. This results in insufficient market value for the products, hindering the large-scale promotion and iterative upgrading of the fiber cement board industry. Summary of the Invention

[0004] The purpose of this invention is to overcome the problems of insufficient toughness, inability to bend significantly, low utilization rate of industrial solid waste, and high production cost of fiber cement boards in the prior art.

[0005] Therefore, the present invention provides a high-toughness bendable fiber cement board, which comprises the following raw materials by weight: 12-25 parts of carbide slag, 35-44 parts of fly ash, 12-20 parts of desulfurized gypsum, 10-25 parts of quartz sand, 0.5-1.5 parts of alkali-resistant glass fiber, 0.8-1.5 parts of PVA fiber, and 3-5 parts of wood pulp fiber.

[0006] Specifically, the calcium hydroxide content in the aforementioned carbide slag is >70%.

[0007] Specifically, the above-mentioned fly ash is secondary fly ash, and the sum of silicon dioxide and aluminum oxide content is greater than 65%.

[0008] Specifically, the aforementioned desulfurized gypsum contains more than 65% dihydrate gypsum.

[0009] Specifically, the length of the alkali-resistant glass fiber is 4-6mm; the length of the PVA fiber is 4-6mm.

[0010] The present invention also provides a method for preparing the above-mentioned high-toughness bendable fiber cement board, comprising the following steps:

[0011] The carbide slag, fly ash, and desulfurized gypsum are ground and pulverized; the quartz sand is ground and sieved separately; and the wood pulp fibers are refined through grinding.

[0012] Loosen the PVA fibers, add pretreated wood pulp fibers and alkali-resistant glass fibers in sequence, stir evenly to obtain composite fibers;

[0013] Mix all dry powder materials evenly, add them to the composite fiber, add water and stir to make a slurry;

[0014] The slurry is molded into a sheet blank;

[0015] The billet is steam cured to obtain a high-toughness, bendable fiber cement board.

[0016] Specifically, grind the carbide slag, fly ash, and desulfurized gypsum to 200-300 mesh.

[0017] Specifically, the particle size of the quartz sand mentioned above is controlled at 70-100 mesh.

[0018] Specifically, the above-mentioned slurry molding process for producing the board blank involves: the slurry being molded using a flow method or a sheet forming method, controlling the uniformity of the blank thickness, eliminating internal air bubbles, and obtaining a dense board blank.

[0019] Specifically, the steam curing conditions mentioned above are 60-80℃ steam environment for 16-24 hours.

[0020] Specifically, the above-mentioned loosening of PVA fibers involves: after loosening and stirring, a single PVA fiber is decomposed into multiple fine fibers with a diameter of 1-9 μm.

[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0022] This invention provides a high-toughness, bendable fiber cement board using a rigid, flexible, and plant fiber ternary composite toughening system, combined with appropriately graded quartz sand and a ternary solid waste-modified matrix structure. This breaks through the bottleneck of traditional fiber cement boards being brittle and inflexible. The board can achieve small-radius circular bending and repeated bending without cracking, significantly improving flexibility and deformation recovery. It is suitable for various curved and irregularly shaped building construction scenarios, broadening its applicability. Through the sulfate activation and micro-expansion effect of desulfurized gypsum, the density of the board matrix is ​​optimized, effectively compensating for board shrinkage deformation and completely solving the problems of warping, micro-cracking, and bending damage in traditional boards. The dimensional stability, flexural strength, and impact toughness of the board are significantly improved, resulting in a longer service life. Furthermore, this formula synergistically utilizes three industrial solid wastes: carbide slag, fly ash, and desulfurized gypsum. The high proportion of solid waste significantly reduces industrial solid waste accumulation pollution, replacing traditional high-energy-consuming cement raw materials, reducing carbon emissions from production, and fully meeting the industry requirements for low-carbon, green, and circular development of building materials.

[0023] The method for preparing high-toughness bendable fiber cement board provided by this invention has a simple production process, is fully compatible with existing production lines, and requires no equipment modification investment. The raw materials are mainly inexpensive industrial solid waste, resulting in low raw material costs. At the same time, the yield rate of the boards and the added value of the products are greatly improved, combining economic and environmental value, and has broad prospects for large-scale promotion. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Although representative embodiments of the present invention have been described in detail, those skilled in the art will understand that various modifications and changes can be made to the present invention without departing from the scope of the present invention. Therefore, the scope of the present invention should not be limited to the embodiments, but should be defined by the appended claims and their equivalents.

[0025] This invention provides a high-toughness, bendable fiber cement board, comprising the following raw materials by weight: 12-25 parts of carbide slag, 35-44 parts of fly ash, 12-20 parts of desulfurized gypsum, 10-25 parts of quartz sand, 0.5-1.5 parts of alkali-resistant glass fiber, 0.8-1.5 parts of PVA fiber, and 3-5 parts of wood pulp fiber.

[0026] The quartz sand is ground to a particle size of 70-100 mesh. Coarse-grained quartz sand optimizes the aggregate gradation within the board, improves the toughness of the matrix skeleton, and avoids the brittleness and easy breakage problems caused by fine sand accumulation, providing a structural basis for the board's bendability. The calcium hydroxide content in the carbide slag is >70%; the fly ash is secondary fly ash with a silica + alumina content >65%; the desulfurized gypsum contains more than 65% dihydrate gypsum; the alkali-resistant glass fiber length is 4-6 mm; the PVA fiber length is 4-6 mm; and the wood pulp fiber is preferably softwood pulp. Ensuring a calcium hydroxide content of no less than 70% in the carbide slag helps provide sufficient calcium raw materials and a suitable alkaline environment, promoting the dissolution of alumina and silica in fly ash and facilitating the secondary pozzolanic reaction of fly ash to generate hydrated cementitious products. A silica and alumina content of >65% in the fly ash ensures sufficient reactants to react with the calcium raw materials, optimizing the matrix microstructure. Common power plant desulfurization gypsum contains over 65% dihydrate gypsum, which can be used directly, ensuring the dissolution of sulfate ions to form a sulfate-activated system, promoting the pozzolanic hydration reaction between carbide slag and fly ash, generating ettringite crystals that produce moderate micro-expansion, filling the capillary pores inside the matrix, effectively compensating for drying shrinkage deformation of the board, and inhibiting the formation of micro-cracks. The ternary solid waste synergistically enhances the matrix strength and structural stability. Fibers longer than 6mm are prone to agglomeration inside the board, compromising its strength; therefore, 4-6mm fibers are preferred. Rigid alkali-resistant fiberglass bears the load and enhances the basic strength of the board. Flexible PVA fiber has excellent tensile toughness and can effectively disperse bending stress. Wood pulp fiber refines the matrix structure and improves the flexibility and fit of the board. The three types of fibers work together to completely solve the pain points of traditional boards being brittle, hard, and unable to be bent, achieving the core characteristics of high strength, high toughness, and large-angle bendability. 70-100 mesh quartz sand is used as aggregate, with moderate coarseness, which can ensure the structural stability of the board without causing excessive rigidity and lack of toughness due to excessively fine aggregate, thus meeting the bending deformation requirements of the board.

[0027] The present invention also provides a method for preparing the above-mentioned high-toughness bendable fiber cement board, comprising the following steps:

[0028] (1) Raw material pretreatment

[0029] Calcium carbide slag, fly ash, and desulfurized gypsum are ground to 200-300 mesh; quartz sand is ground and sieved separately to control the particle size to 70-100 mesh to ensure uniform aggregate particle size; wood pulp fibers are refined through grinding to improve fiber dispersibility.

[0030] (2) Graded blended fiber

[0031] PVA fibers are loosened using a fiber loosening machine to eliminate fiber agglomeration. Pretreated wood pulp fibers and alkali-resistant glass fibers are then added sequentially and stirred at low speeds in stages to obtain well-dispersed and layered composite fibers. This ensures that the various fibers are evenly interwoven to form a three-dimensional toughening network.

[0032] Specifically, after PVA fibers are stirred at 700 rpm for 10 minutes in a fiber loosening machine, a single fiber is broken down into multiple fine fibers with a diameter of approximately 1-9 μm, increasing the fiber count by 4-20 times. This effectively reduces the total fiber content of the board, and the loosened fiber surface is rougher, resulting in stronger adhesion to the matrix surface. The loosening speed and time can be adjusted according to actual conditions to ensure that the fibers are broken down to the required diameter.

[0033] (3) Slurry preparation

[0034] Mix all dry powder materials evenly, add them to the composite fiber, add water and stir for 5-15 minutes to make a uniform and stable slurry without fiber agglomeration.

[0035] (4) Blank forming

[0036] The slurry is formed using the flow method, sheet forming method, or other feasible methods to control the uniform thickness of the blank, eliminate internal air bubbles, and obtain a dense board blank.

[0037] (5) Steam curing

[0038] After pre-curing the green body for 30-60 minutes, it is cured in a steam environment at 60-80℃ for 16-24 hours and then naturally cooled to room temperature to obtain a high-toughness, bendable fiber cement board.

[0039] The effects of the high-toughness bendable fiber cement board and its preparation method of the present invention are studied below through specific embodiments. In the embodiments of the present invention, the calcium hydroxide content in the carbide slag is >70%; the fly ash is secondary fly ash with a silica + alumina content >65%; the desulfurized gypsum contains more than 65% dihydrate gypsum; the alkali-resistant glass fiber length is 4-6 mm; the PVA fiber length is 4-6 mm; and the wood pulp fiber is softwood pulp.

[0040] Example 1:

[0041] This embodiment provides a high-toughness bendable fiber cement board, which, by weight, includes the following raw materials: 20 parts of carbide slag, 40 parts of fly ash, 14 parts of desulfurized gypsum, 20 parts of quartz sand, 1 part of alkali-resistant glass fiber, 1 part of PVA fiber, and 4 parts of wood pulp fiber.

[0042] The above-mentioned high-toughness, bendable fiber cement board is prepared using the following steps:

[0043] (1) Raw material pretreatment

[0044] Grind the carbide slag, fly ash, and desulfurized gypsum to 200-300 mesh; grind and sieve the quartz sand separately, controlling the particle size to 70-100 mesh.

[0045] (2) Graded blended fiber

[0046] PVA fibers are loosened to fine fibers of 1-9μm using a fiber loosening machine to eliminate fiber agglomeration. Pretreated wood pulp fibers and alkali-resistant glass fibers are added in sequence and stirred at low speed in stages to obtain composite fibers with good dispersibility and appropriate layering.

[0047] (3) Slurry preparation

[0048] Mix all dry powder materials evenly, add them to the composite fiber, add water and stir for 10 minutes to make a uniform and stable slurry with no fiber agglomeration.

[0049] (4) Blank forming

[0050] The slurry is formed using the flow method, sheet forming method, or other feasible methods to control the uniform thickness of the blank, eliminate internal air bubbles, and obtain a dense board blank.

[0051] (5) Steam curing

[0052] After pre-curing the billet for 1 hour, it is cured in a steam environment at 60-80℃ for 20 hours and then cooled to room temperature for about 1 hour to obtain a high-toughness, bendable fiber cement board with a thickness of 8mm.

[0053] The performance of the prepared high-toughness bendable fiber cement board was tested using conventional testing methods. Its flexural strength reached 18.5 MPa. It can achieve a radius of 150 mm arc bend without cracking or peeling, and has excellent flexible bending performance. It can be directly applied to irregular decorative construction scenarios such as curved ceilings and arc partitions.

[0054] Example 2:

[0055] This embodiment provides a high-toughness, bendable fiber cement board, comprising the following raw materials by weight: 25 parts carbide slag, 44 parts fly ash, 15 parts desulfurized gypsum, 10 parts quartz sand, 1.5 parts alkali-resistant glass fiber, 1.5 parts PVA fiber, and 3 parts wood pulp fiber. Increasing the content of industrial solid waste and flexible fibers further enhances the board's toughness.

[0056] The above-mentioned high-toughness, bendable fiber cement board is prepared using the following steps:

[0057] (1) Raw material pretreatment

[0058] Grind the carbide slag, fly ash, and desulfurized gypsum to 200-300 mesh; grind and sieve the quartz sand separately, controlling the particle size to 70-100 mesh.

[0059] (2) Graded blended fiber

[0060] PVA fibers are loosened using a fiber loosening machine to eliminate fiber agglomeration. Pretreated wood pulp fibers and alkali-resistant glass fibers are added sequentially and stirred at low speed in stages to obtain composite fibers with good dispersibility and appropriate layering.

[0061] (3) Slurry preparation

[0062] Mix all dry powder materials evenly, add them to the composite fiber, add water and stir for 15 minutes to make a uniform and stable slurry without fiber agglomeration.

[0063] (4) Blank forming

[0064] The slurry is formed using the flow method, sheet forming method, or other feasible methods to control the uniform thickness of the blank, eliminate internal air bubbles, and obtain a dense board blank.

[0065] (5) Steam curing

[0066] After pre-curing the billet for 1 hour, it is cured in a steam environment at 60-80℃ for 16 hours and then cooled to room temperature for about 1 hour to obtain a high-toughness, bendable fiber cement board with a thickness of 8mm.

[0067] The performance of the prepared high-toughness bendable fiber cement board was tested using conventional testing methods. Its flexural strength can reach 17.8MPa, and its impact toughness is 55% higher than that of the traditional 8mm board. It can achieve small-radius arc bending of 120mm without cracking, and repeated bending can be performed without cracking or delamination. It has excellent bending recovery and solves the core defects of traditional 8mm board that cannot be bent at small radius and will crack brittlely after one bend. Its ultra-high toughness is suitable for construction of complex irregular building shapes.

[0068] Example 3:

[0069] This embodiment provides a high-toughness, bendable fiber cement board, comprising the following raw materials by weight: 14 parts carbide slag, 35 parts fly ash, 20 parts desulfurized gypsum, 24.7 parts quartz sand, 0.5 parts alkali-resistant glass fiber, 0.8 parts PVA fiber, and 5 parts wood pulp fiber. This optimizes raw material costs, balancing economy and bending performance, and is suitable for large-scale general applications.

[0070] The above-mentioned high-toughness, bendable fiber cement board is prepared using the following steps:

[0071] (1) Raw material pretreatment

[0072] Grind the carbide slag, fly ash, and desulfurized gypsum to 200-300 mesh; grind and sieve the quartz sand separately, controlling the particle size to 70-100 mesh.

[0073] (2) Graded blended fiber

[0074] PVA fibers are loosened using a fiber loosening machine to eliminate fiber agglomeration. Pretreated wood pulp fibers and alkali-resistant glass fibers are added sequentially and stirred at low speed in stages to obtain composite fibers with good dispersibility and appropriate layering.

[0075] (3) Slurry preparation

[0076] Mix all dry powder materials evenly, add them to the composite fiber, add water and stir for 10 minutes to make a uniform and stable slurry with no fiber agglomeration.

[0077] (4) Blank forming

[0078] The slurry is formed using the flow method, sheet forming method, or other feasible methods to control the uniform thickness of the blank, eliminate internal air bubbles, and obtain a dense board blank.

[0079] (5) Steam curing

[0080] After pre-curing the billet for 1 hour, it is cured in a steam environment at 60-80℃ for 24 hours and then cooled to room temperature for about 1 hour to obtain a high-toughness, bendable fiber cement board with a thickness of 8mm.

[0081] The performance of the prepared high-toughness bendable fiber cement board was tested using conventional testing methods. Its flexural strength can reach 19.2 MPa, and its basic strength is excellent. It can achieve stable bending and forming of a 200 mm radius arc. After bending, the board has good flatness, no warping or micro-cracks. It balances structural strength and bendability, making it suitable for ordinary building curved surface decoration and flexible splicing construction. It has a very high cost performance.

[0082] Existing fiber cement boards have high matrix rigidity and brittleness, with an ultimate bending radius ≥3500mm. This invention eliminates cement and adopts a ternary solid waste cementing system of carbide slag / fly ash / desulfurized gypsum, combined with 70~100 mesh graded quartz sand and multi-element fibers for synergistic toughening, achieving the same or even higher flexural strength while realizing small-radius bending.

[0083] Comparative Example 1:

[0084] This comparative example provides a fiber cement board using a conventional single wood pulp fiber reinforcement system, comprising, by weight, the following raw materials: 37 parts ordinary cement, 56 parts 200-mesh fine quartz sand, and 7 parts wood pulp fiber, without any ternary solid waste modification system. Using conventional processes, the room temperature is raised to 190°C within 9 hours, then cured at 190°C for 10 hours, and cooled for approximately 7 hours to obtain an 8mm fiber cement board.

[0085] The fiber cement board prepared was tested using conventional testing methods. Its flexural strength was 12.3 MPa, and its impact toughness was poor. It could only achieve slight bending at a large radius of 3500 mm or more. Cracking and delamination occurred when bending at a small angle. It could not achieve repeated bending and was completely unsuitable for irregular or curved surface construction scenarios.

[0086] The above examples are merely illustrative of the present invention and do not constitute a limitation on the scope of protection of the present invention. All designs that are the same as or similar to the present invention are within the scope of protection of the present invention.

Claims

1. A high-toughness, bendable fiber cement board, characterized in that, The raw materials include the following by weight: 12-25 parts of carbide slag, 35-44 parts of fly ash, 12-20 parts of desulfurized gypsum, 10-25 parts of quartz sand, 0.5-1.5 parts of alkali-resistant glass fiber, 0.8-1.5 parts of PVA fiber, and 3-5 parts of wood pulp fiber.

2. The high-toughness bendable fiber cement board as described in claim 1, characterized in that: The calcium hydroxide content in the carbide slag is >70%.

3. The high-toughness bendable fiber cement board as described in claim 1, characterized in that: The fly ash is secondary fly ash, and the sum of the contents of silicon dioxide and aluminum oxide is greater than 65%.

4. The high-toughness bendable fiber cement board as described in claim 1, characterized in that: The alkali-resistant glass fiber has a length of 4-6 mm; the PVA fiber has a length of 4-6 mm.

5. The method for preparing the high-toughness bendable fiber cement board according to any one of claims 1-4, characterized in that, Includes the following steps: Calcium carbide slag, fly ash, and desulfurized gypsum are ground and pulverized; quartz sand is ground and sieved separately. The wood pulp fibers are refined through grinding. Loosen the PVA fibers, add pretreated wood pulp fibers and alkali-resistant glass fibers in sequence, stir evenly to obtain composite fibers; Mix all dry powder materials evenly, add them to the composite fiber, add water and stir to make a slurry; The slurry is molded into a sheet blank; The billet is steam cured to obtain a high-toughness, bendable fiber cement board.

6. The method for preparing the high-toughness bendable fiber cement board as described in claim 5, characterized in that: Grind the carbide slag, fly ash, and desulfurized gypsum to 200-300 mesh.

7. The method for preparing the high-toughness bendable fiber cement board as described in claim 5, characterized in that: The quartz sand particle size is controlled at 70-100 mesh.

8. The method for preparing the high-toughness bendable fiber cement board as described in claim 5, characterized in that, The specific process of forming the slurry into a sheet blank involves: forming the slurry using a flow method or a sheet forming method, controlling the uniform thickness of the blank, eliminating internal air bubbles, and obtaining a dense sheet blank.

9. The method for preparing the high-toughness bendable fiber cement board as described in claim 5, characterized in that: The steam curing conditions are 60-80℃ steam environment for 16-24 hours.

10. The method for preparing the high-toughness bendable fiber cement board as described in claim 5, characterized in that, The loosening of PVA fibers specifically involves: PVA fibers being loosened and stirred, with a single fiber decomposing into multiple fine fibers with a diameter of 1-9 μm.